Atherosclerosis of Coronary and Renal Artery Disease in Diabetes Mellitus - Islam, Neena; Haque, KMHS Sirajul; Siddique, Md Abu; Subedi, Bikash; Arzu, Jahanara; Awal, Anisul; Ahmed, Md Khurshed; Fatema, Nilufar; Sultan, Md Ashraf Uddin (University Heart Journal, 2010)
Atherosclerosis is a systemic disease. Although asymmetries in arterial involvement in atherosclerosis may occur, disease usually proceeds in parallel in various organ systems. From a clinical perspective, knowing the prevalence of renal artery involvement in patients with the evidence of atherosclerosis in other organs is important because this knowledge may be incorporated into diagnostic algorithms. This study was aimed to determine the presence of atherosclerotic renal artery disease in diabetes mellitus with coronary artery disease. A total of 173 coronary artery disease patients were purposively selected for the study .Fasting blood sugar level was estimated. Coronary angiograms were performed by standard percutaneous femoral artery cannulation (Judkins Technique).Selective right and left judkins catheter and hand dye injection were used for opacification of renal arteries. Of the 173 study subjects, 143 (diabetic 73) were male and 22 (diabetic 15) were female. Among the diabetic 15 patients had renal artery stenosis and only 7 patients had renal artery stenosis in the non diabetic group. Strength of link between significant renal artery stenosis were strongly correlated (r=0.233, and p, 0.001). Knowledge on the clinical evolution and on the cardiovascular squeal of atherosclerotic renal disease has made substantial progress in recent years. Atherosclerotic renal artery disease is present in significant proportion of diabetic patients undergoing cardiac catheterization for suspected coronary artery disease in comparisons to their non diabetic counter parts. Keywords : Atherosclerosis; Diabetes mellitis; renal artery stenosis DOI: 10.3329/uhj.v5i2.4556 University Heart Journal Vol.5(2) July 2009 pp.63-65